Protocol of mixed-methods assessment of demographic, epidemiological and clinical profile of decentralised patients with cancer at Nelson Mandela Academic Hospital and Rob Ferreira Hospital, South Africa. Issue 4 (21st April 2022) - Chitha, Wezile; Jafta, Zukiswa; Mnyaka, Onke R; Hongoro, Danleen; Godlimpi, Lizo; Swartbooi, Buyiswa; Williams, Natasha; Zungu, Christopher; Buthi, Lazola; Kuseni, Sibulelo; Nasila, John; Sibulawa, Siyabonga; et al.
Abstract : Introduction: Cancer is the second leading cause of death globally. However, cancer care services are often concentrated in urban centres. Two of South Africa's hospitals have decentralised cancer care delivery since February 2018 and August 2019, respectively. This study aims to describe the demographic, epidemiological and clinical profile of various cancers at Nelson Mandela Academic Hospital (NMAH) and Rob Ferreira Hospital (RFH), in South Africa's Eastern Cape and Mpumalanga provinces, respectively. Methods and analysis: This study will be conducted in the Eastern Cape and Mpumalanga provinces. A mixed-methods study design will be undertaken to gain insight on the characteristics of randomly sampled patients who are treated for cancer at NMAH and RFH between 1 March 2018 and 28 February 2022. A validated, researcher-administered survey questionnaire will be used to assess demographic characteristics, and prevalence of different cancers among patients. Concurrently, a document review will be undertaken on patients with cancer using a patient registry to ascertain the duration of diagnosis, type of cancer(s), management plan and patient survival time. STATA V.17 will be used for data analysis. The Shapiro-Wilk test will be used to explore the distribution of numerical variables. The χ 2 or Fisher's exact tests will be used depending on the value of the expected frequencies to compare categorical variables. Kaplan-Meier survival estimates will be used to determine the survival time. Hazard ratios will be used to determine the predictors of death. The level of statistical significance will be set at p value ≤0.05. The 95% CI will be used for the precision of estimates. Ethics and dissemination: Ethics approval was obtained from the Human Research Ethics Committees of the University of the Witwatersrand (M210211) and Walter Sisulu University, South Africa (Ref: 040/2020). Findings will be reported through peer-reviewed journal(s), presentations at conferences and at partner meetings.